2017
DOI: 10.1038/s41467-017-00864-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for IL-1α recognition by a modified DNA aptamer that specifically inhibits IL-1α signaling

Abstract: IL-1α is an essential cytokine that contributes to inflammatory responses and is implicated in various forms of pathogenesis and cancer. Here we report a naphthyl modified DNA aptamer that specifically binds IL-1α and inhibits its signaling pathway. By solving the crystal structure of the IL-1α/aptamer, we provide a high-resolution structure of this critical cytokine and we reveal its functional interaction interface with high-affinity ligands. The non-helical aptamer, which represents a highly compact nucleic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 70 publications
(94 reference statements)
2
44
0
Order By: Relevance
“…Ren et al (36) recently conducted a crystallization experiment using IL-1a and IL-1b specific binding with a modified DNA aptamer (SL1067) with 2-naphthylmethyl substitutions at the 5-position of deoxyuridine (2Nap-dU) in order to solve the crystal structure of IL-1a. They observed that IL-1a binds to SL1067 with 7.3 mM affinity, whereas IL-1b shows no interaction, suggesting that IL-1a has intrinsic properties to bind DNA without a cointeracting protein to assist in transcription regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Ren et al (36) recently conducted a crystallization experiment using IL-1a and IL-1b specific binding with a modified DNA aptamer (SL1067) with 2-naphthylmethyl substitutions at the 5-position of deoxyuridine (2Nap-dU) in order to solve the crystal structure of IL-1a. They observed that IL-1a binds to SL1067 with 7.3 mM affinity, whereas IL-1b shows no interaction, suggesting that IL-1a has intrinsic properties to bind DNA without a cointeracting protein to assist in transcription regulation.…”
Section: Discussionmentioning
confidence: 99%
“…A total of six ssDNA aptamer probes with a length of 86 nt were identified using multiple sequence alignment analysis by DNAMAN software. Considering the important role that secondary structures play in the recognition capacity of aptamers 48 , 49 , the secondary structures of the six selected aptamer probes were also analyzed and found to be composed of various stem-loop and hairpin structures ( Figure S3 ). Probes sk1, sk2, sk3, sk4, sk5, and sk6 accounted for 50%, 3.3%, 13.3%, 16.7%, 13.3%, and 3.3% of all positive clones, respectively ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Enhancement in the chemical diversity of these random nucleic acid libraries, even with one and the same modification at only one of the four bases (e.g., at a 5-position of a pyrimidine throughout the library), can dramatically improve both the success rate of DNA-based SELEX experiments and the binding affinities of the resulting aptamers (14)(15)(16). Crystal structures of these SOMAmer reagents (slow offrate modified aptamers) bound to their cognate proteins make it clear that the pyrimidine adducts of SOMAmers form direct contacts with the protein and participate in shaping the binding interface, much like amino acid residues in proteins (17)(18)(19)(20)(21). As importantly, these crystal structures also show that the hydrophobic "side chains" of the modified bases participate in internal motifs that stabilize the folded structures (19).…”
Section: Discussionmentioning
confidence: 99%